Malignant peripheral nerve sheath tumour with metastasis and expression of endothelial differentiation factors in a horse. (24th June 2017) - Bouéres, C. S.; Câmara, A. C. L.; Castro, M. B.; Barbosa, E. F.; Souza, C. A.; Serakides, R.; Teixeira Neto, A. R.
Summary: Malignant peripheral nerve sheath tumour (MPNST) has not previously been well documented in veterinary literature. This article reports the case of a 12‐year‐old Mangalarga Marchador gelding presented for evaluation of a large, ulcerated and pruritic lesion in the elbow of the left forelimb. Biopsy of the mass indicated an undifferentiated sarcoma. Considering the chronicity of the condition, poor prognosis and extensive nature of the neoplasm, the horse was subjected to euthanasia. A MPNST with expression of endothelial differentiation factors was diagnosed based on gross morphology results, histological features and immunohistochemical findings.